(untitled) (The Pretoria Student Law Review, 2021)
This article reflects on the possible future of labour law as a response to industrialisation, particularly the 4IR. First, I discuss the origin of the industrial revolution by reflecting on the first three industrial revolutions and the present 4IR. Second, I reflect on; 1) the possible impact of the 4IR on the employment relationship and 2) the new and/or adaptive skills requirements. Third, I present recommendations to respond to the fast-changing pace of labour and industrialisation suggested by the World Economic Forum (WEF). I thereafter conclude that the 4IR may be used as a vehicle to promote a socially affirmative interpretation of fairness in the labour context. This promotes a constitutional obligation to protect the interests of workers, in light of technological advancement, that have the potential to widen the income inequality gap.